Exploring the Value of the Prehistoric Cultural Site of Sanya from the Perspective of the B & R Initiative - Lijun ZHANG; Chaorong LI; Minsheng LIAO (Haiyang Kaifa yu guanli, 2022)
The prehistoric cultural sites of Sanya have important natural and humanistic scientific values, being the source of Hainan′s marine culture. The "Luobi Cave Site" → "Xianlang Cave Site" → "Yingdun Site" shows the development process of Sanya′s prehistoric humans living to the sea. Based on the systematically collected and sorted out prehistoric archaeological data of Hainan Province, this paper sorted out the research of Sanya′s prehistoric cultural sites from the perspective of the "Belt and Road Initiative", excavated their cultural connotation and core values, and put forward countermeasures and suggestions for the protection, development and utilization of prehistoric cultural heritage, so as to meet the needs of Hainan to build the "21st Century Maritime Silk Road" culture, and also provided reference for related academic research and the inheritance, protection and value dissemination of cultural heritage.